Problems and Possibilities for Physical Education Management in Selected High Schools in Guizhou, China - Li, Xiaolan (Pacific International Journal, 2025)
The management of Physical Education (PE) in high schools faces significant challenges in the post-pandemic era, particularly in developing regions like Guizhou, China. This study investigates the specific problems and possibilities in PE management as perceived by the teachers implementing these programs. Methods:​ A quantitative survey was administered to 55 PE teachers from three high schools in Guizhou. The questionnaire assessed their perceptions of challenges and potential solutions across five domains: budget management, resource allocation, professional development, teaching strategies, and curriculum design. Data were analyzed using descriptive statistics and correlational analysis. Results:​ Teachers identified budget management and allocation as the most significant challenge (M=2.71), while also rating it as the area with the lowest potential for immediate resolution. In contrast, curriculum design and innovation were seen as a moderate challenge (M=3.01) but held the highest potential for improvement. A significant positive correlation was found between teachers' assessment of challenges and their belief in the possibility of addressing them. Discussion:​ The findings indicate that while systemic issues like funding are major obstacles, teachers are optimistic about solutions within their control, particularly pedagogical innovation. The study concludes that effective PE management improvement should involve strategic budget advocacy by administrators while empowering teachers to develop context-specific, innovative curricula that maximize existing resources.